MODEL PEMBELAJARAN DICK AND CAREY SERTA IMPLEMENTASINYA DALAM PEMBELAJARAN PAI - Mashudi; Dila Rukmi Octaviana; Sutomo, Moh (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
Dick and Carey's learning model is a learning model developed through a systems approach. The learning system model developed by Dick and Carey consists of several components that are necessary to design larger learning activities. Dick and Carey include cognitive and behavioristic elements that emphasize students' responses to the stimulus presented. The steps of the Dick and Carey model are 10 systematic steps. This model is suitable to be applied in PAI learning because the stages in this model are detailed and structured so that they can produce better learning and are in accordance with the core competencies in PAI learning, namely mastery of knowledge, attitudes and skills, in addition to PAI learning orientation which is oriented towards human nature, namely the body, mind and spirit that must be maintained in order to achieve balance (tawazun), so that it requires a complete and detailed process of designing learning. This research uses literature research (Library Research). The purpose of this study was to determine the understanding and brief history of the Dick and Carey model, to find out the steps in the Dick and Carey learning design model, to determine the implementation of the Dick and Carey learning model in PAI learning, to determine the advantages and disadvantages of the Dick and Carey design model Carey.